2019
DOI: 10.1096/fj.201801798rr
|View full text |Cite
|
Sign up to set email alerts
|

miR‐22 and miR‐214 targeting BCL9L inhibit proliferation, metastasis, and epithelial‐mesenchymal transition by down‐regulating Wnt signaling in colon cancer

Abstract: The epithelial‐mesenchymal transition (EMT) is crucial for cancer progression. Evidence has shown that miR‐22 and miR‐214 play a key role in colon cancer progression; however, the underlying mechanism remains to be known. The effects of miR‐22 and miR‐214 on EMT are contradictory in different cancers, and whether miR‐22 and miR‐214 are involved in the colon cancer EMT process needs to be elucidated. In this study, we evaluated the exact role and the regulation mechanism of miR‐22 and miR‐214 in colon cancer. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…27 Besides, miR-214 sensitized CC cells to irradiation by suppression of ATG12-regulated autophagy. 28 Even though miR-214 was corroborated to inhibit CC tumor growth in nude mice, 29 its connection with metastasis in vivo remains unclear. Our microarray analysis revealed that miR-214 was one of the most significantly downregulated miRNAs in CC.…”
Section: Discussionmentioning
confidence: 99%
“…27 Besides, miR-214 sensitized CC cells to irradiation by suppression of ATG12-regulated autophagy. 28 Even though miR-214 was corroborated to inhibit CC tumor growth in nude mice, 29 its connection with metastasis in vivo remains unclear. Our microarray analysis revealed that miR-214 was one of the most significantly downregulated miRNAs in CC.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that miR-214 significantly promoted the EMT process of melanoma, while CADM1 inhibited the EMT process. These results were similar to those of previous studies ( 46 48 ), thus indicating that miR-214 increased the invasion and migration of melanoma by downregulating CADM1 to promote the EMT process. However, it has also been revealed that miR-214 promotes cancer progression by activating the NF-κB signaling pathway ( 49 ).…”
Section: Discussionsupporting
confidence: 92%
“…MiR-214-3p is involved in many pathological and physiological processes, such as cell growth, migration, proliferation, invasion, apoptosis, and fibrosis. 51,52 Our previous study also demonstrated that miR-214-3p plays an important role in regulating cardiac pyroptosis by binding to the caspase-1 during diabetic cardiomyopathy progression. 28 Moreover, consistent with the present study, our previous report has documented that the level of miR-214-3p is significantly decreased in patients with DM, 53 which is in agreement with the published data by other groups, 54,55 suggesting the possible implication of our findings in humans.…”
Section: Discussionmentioning
confidence: 91%